The Mark Coventry Award: Custom Cutting Guides Do Not Improve Total Knee Arthroplasty Clinical Outcomes at 2 Years Followup. Issue 1 (January 2016) - Nam, Denis; Park, Andrew; Stambough, Jeffrey B.; Johnson, Staci R.; Nunley, Ryan M.; Barrack, Robert L.
Abstract: Background: Custom cutting guides (CCGs; sometimes called patient‐specific instrumentation [PSI]) in total knee arthroplasty (TKA) use preoperative three‐dimensional imaging to fabricate cutting blocks specific to a patient's native anatomy. Questions/purposes: The purposes of this study were to determine if CCGs (1) improve clinical outcomes as measured by UCLA activity, SF‐12, and Oxford knee scores; and (2) coronal mechanical alignment versus standard alignment guides. Methods: This was a retrospective cohort study of patients undergoing primary TKA using the same cruciate‐retaining, cemented TKA system between January 2009 and April 2012. Patients were included if they were candidates for a unilateral, cruciate‐retaining TKA and met other prespecified criteria; patients were allowed to self‐select either an MRI‐based CCG procedure or standard TKA. Ninety‐seven of 120 (80.8%) patients in the standard and 104 of 124 (83.9%, p = 0.5) in the CCG cohort with a minimum of 1‐year followup were available for analysis. The first 95 patients in the standard (mean followup, 3 years; range, 1‐4 years) and CCG (mean followup, 2 years; range, 1‐4 years) cohorts were compared. The alignment goal for all TKAs was a hip‐knee‐ankle (HKA) angle of 0°. UCLA, SF‐12, and Oxford knee scores were collected preoperatively and at each patient's most recent followup visit. Postoperative, rotationally controlled coronal scout CT scans were used to measure HKA alignment. Independent‐sample t‐tests and chi‐square tests were used for comparisons with a p value ≤ 0.05 considered significant. Results: At the most recent followup, no differences were present between the two cohorts for range of motion (114° ± 14° in CCG versus 115° ± 15° in standard, p = 0.7), UCLA (6 ± 2 in CCG versus 6 ± 2 in standard, p = 0.7), SF‐12 physical (44 ± 12 in CCG versus 41 ± 12 in standard, p = 0.07), or Oxford knee scores (39 ± 9 in CCG versus 37 ± 10 in standard, p = 0.1). No differences were present for the incremental improvement in the UCLA (1 ± 4 in CCG versus 1 ± 3 in standard, p = 0.5), SF‐12 physical (12 ± 20 in CCG versus 11 ± 21, p = 0.8), or Oxford knee scores (16 ± 9 in CCG versus 19 ± 10 in standard, p = 0.1) from preoperatively to postoperatively. There was no difference in the percentage of outliers for alignment (23% in standard versus 31% in CCG with HKA outside of 0° ± 3°; p = 0.2) between the two cohorts. Conclusions: At a mean followup of greater than 2 years, CCGs fail to demonstrate any advantages in validated knee outcome measure scores or coronal alignment as measured by CT scan versus the use of standard instrumentation in TKA. The clinical benefit of CCGs must be proven before continued implementation of this technology. Level of Evidence: Level III, retrospective controlled study.